Evaluasi Skema Kredit terhadap Peningkatan Profitabilitas - Zulfatun Ruscitasari; Noris Noris; Galuh Ratna Mutia (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
This study aims to identify the accounting information system for providing credit to the profitability of the Dewi Kunti Women's Cooperative. The research data collection method was obtained from interview techniques and data documentation, while the data sources used primary data and secondary data. The qualitative descriptive data analysis technique was chosen as the method of analysis in this study. This was done by analyzing financial ratios, namely the ratio of liquidity, solvency, profitability, and activity ratio. The results of the research based on the results of interviews with the Dewi Kunti Women's Cooperative show that there are two reasons that influence credit to profitability, namely the lack of analysis of how the credit scheme is applied to the Dewi Kunti Women's Cooperative and policies on how the effectiveness of the credit scheme in increasing profitability, but in the procedure for granting credit more optimized to prevent problem loans.